PENGARUH PENAMBAHAN ASAP CAIR TERHADAP PERUBAHAN MUTU NIRA AREN SELAMA PENYADAPAN DAN PENYIMPANAN - Tubagus Bahtiar Rusbana (Jurnal Agroekoteknologi, 2009)
ABSTRACTPalm juice as a raw material of brown sugar can be fermented easly. Smoke is used traditionally as an alternative indirect way to preserve the palm juice. Preservation of palm juice using liquid smoke directly have never been conducted before. The aim of this study is to investigate the effects of liquid smoke on palm juice preservation. First step, the liquid smoke was redestilated. Then, 0,50%, 1,00%, 1,50%, 2,00%, and 3,00%(v/v) concentration of liquid smoke was applied on palm juice when tapping and storage. It showed that the liquid smoke with concentration under 0,5% (v/v) cannot preserve the palm juice during 12 hours storage. 1% until 3% liquid smoke can preserve the palm juice during 12 hours storage. In fact, the pH of palm juice with liquid smoke increased when it was tapped, but the pH of palm juice without liquid smoke decreased certainly. The concentration of liquid smoke 1% and 3% could preserve the pH of palm juice above 6. That indicated the palm juice could be processed become brown sugar.Key Words: Liquid Smoke Palm Juice, Tapping, and Storage